Brazilian Investments Funds: the influence of higher moments in performance evaluation - Milani, Bruno; Ceretta, Paulo Sérgio; Galvão de Barba, Fernanda; Casarin, Fernando (Review of Business Management, 2010)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The mutual fund industry plays an important role in picking up and allocating resources in the Brazilian market. Its importance increased significantly after the country’s economic opening, as well as the number of funds an it’s amount of resources under management. The main models of portfolio’s performance evaluation are conditioned to the assumption of normality of returns distribution and the relation between the first and the second moment, like the traditional CAPM model. But, the normality is not always observed and the inclusion of superior moments in the model may be interesting to catch the systematic skewness and kurtosis effect. In the present article, the co-skewness and co-kurtosis variables are added to the CAPM model. Several regressions are estimated by the ordinary least squares method, applied into the Brazilian mutual fund context. The results point out that the addition of superior moments in the national context, is not very relevant. In order to validate the study, two alternative sub-samples were made, in which the results kept the same. Key words: <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Mutual funds. Performance. Superior moments.